Global models of ant diversity suggest regions where new discoveries are most likely are under disproportionate deforestation threat - Guénard, B.; Weiser, M. D.; R., Dunn R. (PNAS, 2012)
Most of the described and probably undescribed species on Earth are insects. Global models of species diversity rarely focus on insects and none attempt to address unknown, undescribed diversity. We assembled a database representing about 13,000 records for ant generic distribution from over 350 regions that cover much of the globe. Based on two models of diversity and endemicity, we identified regions where our knowledge of ant diversity is most limited, regions we have called “hotspots of discovery.” A priori, such regions might be expected to be remote and untouched. Instead, we found that the hotspots of discovery are also the regions in which biodiversity is the most threatened by habitat destruction. Our results not only highlight the immediate need for conservation of the remaining natural habitats in these regions, but also the extent to which, by focusing on wellknown groups such as vertebrates, we may fail to conserve the far greater diversity of the smaller species yet to be found.
Owner: AdminNUSAdded to JabRef: 2013.06.08
Keywords: ants; global models